Magnetism Basics and Applications - Stefanita, Carmen-Gabriela.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This textbook is aimed at engineering students who are likely to come across magnetics applications in their professional practice. Whether designing lithography equipment containing ferromagnetic brushes, or detecting defects in aeronautics, some basic knowledge of 21st century magnetism is needed. From the magnetic tape on the pocket credit card to the read head in a personal computer, people run into magnetism in many products. Furthermore, in a variety of disciplines tools of the trade exploit magnetic principles, and many interdisciplinary laboratory research areas cross paths with magnetic phenomena that may seem mysterious to the untrained mind. Therefore, this course offers a broad coverage of magnetism topics encountered more often in this millenium, revealing key concepts on which many practical applications rest. Some traditional subjects in magnetism are discussed in the first half of the book, followed by areas likely to spark the curiosity of those more interested in today$1 (Bs technological achievements. Although sometimes some aspects may seem difficult to comprehend at first, bibliography directs the reader to appropriate further study. Throughout the chapters, the student is encouraged to discover the not-so-obvious associations between different magnetics topics, a task that will prove to be at the very least rewarding.s
Traditional Magnetism -- The Magnetization Process. Micromagnetism -- Magnetic Nondestructive Testing Techniques -- Uses of the Magneto-Optical Effect -- Magnetoelectric Materials -- Giant Magnetoresistance, Spin Valves -- Introduction to Spintronics -- Some Magnetic Recording Media Developments -- Concluding Remarks.
Keywords: Physics; Magnetism; Engineering; Nanotechnology; Physics; Magnetism, Magnetic Materials; Nanotechnology; Engineering, general